2001
DOI: 10.1246/cl.2001.918
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of the Ru(H)2(CO)(PPh3)3-Catalyzed Addition of C–H Bonds in Aromatic Esters to Olefins

Abstract: The reaction mechanism of the Ru(H)2(CO)(PPh3)3-catalyzed addition of C–H bonds in aromatic esters to olefins was studied by means of deuterium-labeling experiments and measurement of the 13C kinetic isotope effect. The deuterium-labeling experiment revealed a rapid equilibrium among the intermediates prior to the reductive elimination, and the 13C NMR kinetic isotope effect indicated that C–C bond formation is the rate-determining step in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…The studies of 13 C KIE for this coupling reaction also provide support that the reductive elimination step is rate-determining. [28] Thus, Murai×s experimental results are consistent with Morokuma×s theoretical calculation. [27] 9 Brookhart found another important phenomenon for the chelation-assisted C À H/olefin couplings.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The studies of 13 C KIE for this coupling reaction also provide support that the reductive elimination step is rate-determining. [28] Thus, Murai×s experimental results are consistent with Morokuma×s theoretical calculation. [27] 9 Brookhart found another important phenomenon for the chelation-assisted C À H/olefin couplings.…”
supporting
confidence: 79%
“…(28). [57] Miura found that the reaction of phenylboronic acid with excess amounts of norbornene using [RhCl(cod)] 2 /DPPP [DPPP 1,2-28 REVIEWS Fumitoshi Kakiuchi, Naoto Chatani bis(diphenylphophino)propane] as catalyst results in multiple substitution with norbornene on aromatics in high yield (Scheme 3).…”
mentioning
confidence: 99%
“…In accord with this result, coupling reactions showed a significant 13 C KIE (for the ortho carbon) implicating C-C coupling as the rate-determining step (119). In an unusual example of chemoselectivity in this system, only aryl esters with electron-withdrawing groups undergo coupling (120) (whereas aryl ketones tolerate electron-withdrawing and -donating groups).…”
Section: Figure 5 Mechanism Proposed By Murai For Ru(0)-catalyzed "Ssupporting
confidence: 52%
“…The carbonyl group in aromatic esters [33,34], aldehydes [35], and amides [36] can also function as a directing group. In the studies of alkylations of these aromatic compounds, several important features of the catalytic alkylation of C -H bonds have been revealed.…”
Section: Equation 3 Equationmentioning
confidence: 99%
“…In the studies of alkylations of these aromatic compounds, several important features of the catalytic alkylation of C -H bonds have been revealed. Murai and coworkers investigated the reaction mechanism by means of deuterium-labeling experiments and the 13 C kinetic isotope effect at natural abundance [34]. They revealed that there is a rapid equilibrium between the intermediates prior to the C -C bond formation step, i.e., a reductive elimination step, and that the C -C bond formation is rate-determining in the catalytic cycle (Scheme 7).…”
Section: Equation 3 Equationmentioning
confidence: 99%